Perbandingan Kedudukan Penyidik Tindak Pidana Narkotika Menurut Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika Dan Kitab Undang-Undang Hukum Pidana - Hutagaol, Ramses (Universitas Medan Area, 2019)
The existence of Authority between Investigators of the National Narcotics Agency and the Republic of Indonesia Police Article 81 of Law Number 35 Year 2009 concerning Narcotics, especially in the field of investigation, causes a dualism in the investigation of narcotics crime. The authority of the Narcotics Agency in Law Number 35 of 2009 has a greater portion than the Police Discipline. The regulatory authority for the investigation of the National Narcotics Agency in Law Number 35 Year 2009 concerning National Narcotics in the context of preventing the development of increasingly organized narcotics crime. In addition good coordination needs to be continued between the police and PPNS BNN. In order for the Government to make laws and regulations governing the limits of authority between law enforcement agencies such as the PPNS National Narcotics Agency and the National Police so that there are no differences in interpretation and investigation dualism.